Comparison of NO x reduction among different coal combustion methods and the application of decoupling combustion - Shang, X.; Gao, S.; Wang, Y.; Dong, Li; Xu, G.; Guo, J. (2012)
The reduction of NO x emission via different coal combustion methods was studied in a two-stage reactor using 3 different coals. The NO x formation is effectively suppressed by reburning the gas from pyrolysis and partial gasification of coal, making the NO x emission obviously lower than that of the air-staged combustion. It is found that the decoupling combustion leads to the higher NO x reduction rate, which is over 32% in comparison with the normal combustion. The NO x reduction rates vary with the coal properties. The smaller the fuel ratio (fixed carbon to volatile matter)at per nitrogen content in coal, the lower NO x emission is for reburning the combustible gas from pyrolysis and gasification and also for the decoupling combustion. The NO x emission due to reburning the partial gasification gas varies with the oxygen amount applied in the gasification, and the lowest NO x emission is realized in the oxygen concentration from 8% to 10%. A 1.4 MW industrial boiler was designed according to the principle of the decoupling combustion technology. The running data for the same coal show that the decoupling combustion reduces 32.9% NO x emission in comparison with the traditional combustion.